The Role of Customer Payment Trends in Shaping Cash Flow Forecasts for Digital Commerce Businesses - Suciati, Suciati (Journal of Social Commerce, 2025)
Because digital commerce is unpredictable, managers need to pay special attention to cash flow forecasting. We examine different ways payments by customers are changing, particularly through Buy Now Pay Later, digital wallets, regional variations and subscriptions and their effects on controlling cash flow timing and consistency. The research examines the impact of new payment options by first reviewing 30 interviews with financial and operational professionals from many e-commerce firms and then by studying five comparative case studies. It is shown that today’s forecasting includes more than just numbers and a look at past data; instead, it involves many functions in the business and technology, laws and consumer habits. It introduces a new approach to thinking about cash flow forecasting and outlines ways for companies to manage the uncertainty arising from digital finance.